ANALISIS KESIAPAN MAHASISWA DALAM MENGGUNAKAN AI UNTUK MENDUKUNG PROSES PEMBELAJARAN MAHASISWA UNISNU JEPARA - Muhaimin, Muh (Tunas Nusantara, 2024)
This study aims to analyze the preparedness of students in facing the implementation of Artificial Intelligence (AI) technology in education. With the advancement of technology, AI is increasingly being used to support the learning process, both in the form of AI-based learning applications and in the development of adaptive educational systems. However, the adoption of this technology requires readiness from various parties, especially students as the primary users. This research uses a survey method by collecting data from students across different study programs to measure their understanding, skills, and attitudes toward AI. The results show that although most students are aware of the importance of AI in education, there are significant differences in their readiness in terms of technical skills and acceptance of AI use in academic activities. Therefore, this study suggests the need for enhanced education and training related to AI so that students can optimally utilize it to support their learning process.Keywords: Education and Technology, Student Readiness, Artificial Intelligence (AI)